2013
DOI: 10.1186/1471-2148-13-238
|View full text |Cite
|
Sign up to set email alerts
|

The vertebrate ancestral repertoire of visual opsins, transducin alpha subunits and oxytocin/vasopressin receptors was established by duplication of their shared genomic region in the two rounds of early vertebrate genome duplications

Abstract: BackgroundVertebrate color vision is dependent on four major color opsin subtypes: RH2 (green opsin), SWS1 (ultraviolet opsin), SWS2 (blue opsin), and LWS (red opsin). Together with the dim-light receptor rhodopsin (RH1), these form the family of vertebrate visual opsins. Vertebrate genomes contain many multi-membered gene families that can largely be explained by the two rounds of whole genome duplication (WGD) in the vertebrate ancestor (2R) followed by a third round in the teleost ancestor (3R). Related chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(151 citation statements)
references
References 69 publications
(115 reference statements)
14
135
0
Order By: Relevance
“…The chromosomal locations of the CRH family genes show that they are located in two distinct paralogons: CRH1, CRH2, and UCN1 reside in the same paralogon as the previously described opioid peptide and receptor genes (Dreborg et al 2008, Sundstrom et al 2010, Larhammar et al 2015, and the UCN2 and UCN3 genes are located in the paralogon harboring the visual opsin and oxytocin/ vasopressin receptor genes (Lagman et al 2013) (Fig. 3).…”
Section: Analyses Of Neighboring Gene Familiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The chromosomal locations of the CRH family genes show that they are located in two distinct paralogons: CRH1, CRH2, and UCN1 reside in the same paralogon as the previously described opioid peptide and receptor genes (Dreborg et al 2008, Sundstrom et al 2010, Larhammar et al 2015, and the UCN2 and UCN3 genes are located in the paralogon harboring the visual opsin and oxytocin/ vasopressin receptor genes (Lagman et al 2013) (Fig. 3).…”
Section: Analyses Of Neighboring Gene Familiesmentioning
confidence: 99%
“…For each of the CRH family members, we also identified and analyzed gene families with members in the same chromosomal regions. This showed that the CRH family genes are located in two paralogons (sets of related chromosome regions), which have been previously analyzed in detail by us, namely the paralogon that contains the opioid peptide and receptor genes (Dreborg et al 2008, Sundstrom et al 2010, Larhammar et al 2015 and the one that contains the visual opsin genes and the oxytoc in and vasopressin receptor genes (Lagman et al 2013). This allowed us to distinguish orthologs and paralogs for the CRH family genes and to deduce that the CRH fami ly duplications took place as part of the basal vertebrate tetraploidizations (with one additional copy arising in the teleost tetraploidization, see below).…”
Section: Crh Gene Family Members In Vertebratesmentioning
confidence: 99%
See 3 more Smart Citations